Analisis Asumsi-Asumsi pada Program Food Estate di Papua - Beltahmamero Simamora; Khairunnisah Lubis; Hadiyanti Arini (Universitas Medan Area, 2021)
The issue of the food crisis sticking out long before the Covid-19 pandemic occurred since 2008 and has become a hot topic discussed by regional and global institutions. The recommendation to maximize the private or corporate sector with the support of global scale financialization to move investment in the field of food production is one of the